1991
DOI: 10.1159/000204800
|View full text |Cite
|
Sign up to set email alerts
|

Megakaryocytic Phagocytosis in a Chromosomally Normal Neonate with Transient Myeloproliferative Disorder

Abstract: We report a case of transient myeloproliferative disorder (TMD) involving the megakaryocytic lineage in a cytogenetically normal newborn infant. Prominent megakaryocytic phagocytosis in the bone marow was observed. This finding might suggest that TMD was due to a self-limiting malignant clone in myelopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
0
1
Order By: Relevance
“…The results of this light microscopy study showed that the cells participating in ME were mostly neutrophil granulocytes and that there was no morphological change in the structure of these cells. In contrast to studies that regarded emperipolesis as phagocytosis,27–29 in the present study no phagosome, the definitive feature of phagocytosis, was observed. In previous light and electron microscopy studies performed on rat and mouse bone marrow, the morphological structures of megakaryocytes and the cells engulfed by them were found to be normal and emperipolesis was defined as being different from phagocytosis 4, 16, 30.…”
Section: Resultscontrasting
confidence: 99%
“…The results of this light microscopy study showed that the cells participating in ME were mostly neutrophil granulocytes and that there was no morphological change in the structure of these cells. In contrast to studies that regarded emperipolesis as phagocytosis,27–29 in the present study no phagosome, the definitive feature of phagocytosis, was observed. In previous light and electron microscopy studies performed on rat and mouse bone marrow, the morphological structures of megakaryocytes and the cells engulfed by them were found to be normal and emperipolesis was defined as being different from phagocytosis 4, 16, 30.…”
Section: Resultscontrasting
confidence: 99%